Terpyridine-functionalized surfaces redox-active, switchable, and electroactive nanoarchitecturesgland - Winter, Andreas (Advanced materials (Deerfield Beach, Fla.), 2011)
Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.